Atlas of medieval Europe - Ditchburn, David 1961-; MacLean, Simon; MacKay, Angus 1939- (Routledge, 2007)
"The Atlas of Medieval Europe covers the period from the fall of the Roman Empire through to the beginnings of the Renaissance, spreading from the Atlantic coast to the Russian steppes. Each map approaches a separate issue or series of events in medieval history, and a commentary locates it in its broader context."